Applying Think-Pair-Share Model in Vocabulary Learning - Muhamad Ihsan (English Education Department, 2019)
This research aims at finding out whether thinkpair-share model of learning can be applied to improve the vocabulary mastery of the second semester of PAI 1 FTIK IAIN Palu. The researcher focused the vocabulary learning with the objectives: 1) to know the meaning of the words; 2) to know the pronunciation of the words; 3) to know the category of the words; and 4) to know how to use the words in sentences or contexts. The subject of this research was 20 students of the second semester of PAI 1 FTIK IAIN Palu. This was a classroom action research which was done in two months. The researcher applied two cycles during the research. The result of the research shows that the application of think-pair-share model can improve the vocabulary learning of the the second semester of PAI 1 FTIK IAIN Palu. This can be proven by the increase from 8 students (40%) in cycle 1 to 15 students (75%) who got score greater than 75 of 20 students in cycle 2. The treatment was stopped after 75% of the classical achievement has met the criteria of success. Therefore, the application of think-pair-share technique was effective to improve the vocabulary mastery.